2012
DOI: 10.1016/j.jbi.2012.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Design for risk control: The role of usability engineering in the management of use-related risks

Abstract: The majority of medical device incident reports can primarily be attributed to use error. Greater attention to human factors and usability during development of a medical device could improve this situation. However, recent studies have shown that companies do not find the application of a sound usability engineering process according to international standards a simple task. The purpose of this collaborative research project between a medical device company, two universities and a university hospital was to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…In accordance with the increasing focus on usability in product development and case studies reporting on its practical implementation [16], we undertook iterative design methods to create an updated system aimed at addressing the shortcomings of the initial version as well as the current state-of-the-art LFA reader technology.…”
Section: Methodsmentioning
confidence: 99%
“…In accordance with the increasing focus on usability in product development and case studies reporting on its practical implementation [16], we undertook iterative design methods to create an updated system aimed at addressing the shortcomings of the initial version as well as the current state-of-the-art LFA reader technology.…”
Section: Methodsmentioning
confidence: 99%
“…In practice, user research tends to be conducted at the product review stage [8]. Studies suggested that conducting user research at the early stage of the design will reduce subsequent development cost and time overrun [91], [92]. Although the above studies underlay the influencing factors by validating the completed products with targeted users, the studies do not provide any framework to apply those finding factors to medical device development.…”
Section: User Acceptance Of the Iot Device In Medical And Well-being Applicationmentioning
confidence: 99%
“…Several studies generally refer to the FDA guidance to ensure that the device under development will meet the standard requirements [97], [98], [101]- [103]. Some of the existing studies [92], [104], [105], and standard [106] have laid their focus on users as a center of the design.…”
Section: The New Product Development Process (Npd) For Medical Device Development (Mdd)mentioning
confidence: 99%
“…Drug device performance includes: i) usability of the device, that should be intuitive, not prone to errors, effective and efficient administration with the appropriate instructions and training; ii) syringeabilty of the drug product that should easily pass through a hypodermic needle to enable ease of withdrawal without drug product clogging and foaming tendencies; iii) injectability of the drug product that must ensure accurate dose, and ease of administration with reduction of pain or other adverse reactions. 37,38 The device injectability will be defined by the drug product's rheological behavior which is subject to the nature of the drug formulation and will affect delivery performance, e.g., force required for injection, uniformity of flow, and freedom from needle blockage. The device constituent parts will define the device performance together with the drug product to guide CP development.…”
Section: Drug Biologic and Device Combination Productsmentioning
confidence: 99%